An analysis of activities that develop pragmatic competence skills among English language learners - Azhar Wazir Thealib Al-Mayali (Humanities Horizon, 2026)
Pragmatic competence is very important for English language learners. Learners of any foreign language must know how to use language, vocabulary, expressions, and gestures within specific contexts. Learning a language involves more than just vocabulary and grammar; it also includes pragmatic abilities, which are the capacity to understand and convey the implicit meanings of the language Therefore, this study focused on explaining and analyzing some activities that can develop the communicative ability of English language learners, as these activities are an important part of the language learning process. This study examines activities designed to develop pragmatic competency among ASL learners in school settings. It aims to identify effective strategies that enhance learners’ communicative skills. A qualitative analysis of selected classroom activities was conducted. The findings indicate that interactive and context-based activities significantly improve pragmatic use of ASL. The study highlights the importance of incorporating pragmatic-focused tasks in ASL instruction.